Pengaruh Bimbingan Belajar dan Pengawasan Orang Tua terhadap Motivasi Belajar Siswa di Kawasan Industri Kota Tenggarong - Sugianto, Sugianto (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
Guidance services in schools are one way to motivate student learning in schools, therefore guidance programs must always be owned or run in every educational unit. Likewise the role of parents at home in terms of supervision of learning for children, with environmental conditions in industrial estates, busy parents and lack of supervision, which greatly influences their motivation to learn. But among the teachers and parents, there are some who have carried out tutoring and supervision of their children. This study aims to determine the effect of tutoring and parental supervision together (simultaneous) on students' motivation to study in Public Elementary Schools in Tenggarong industrial area. This research is a Field Work Recearch (field research) with a quantitative / statistical approach with a population of 107 students of class V and VI of State Elementary School 006 and 016 Tenggarong with a sample of 84 respondents obtained from sampling using the Proportionate Stratified Random Sampling technique. The instrument used in the form of a questionnaire / questionnaire and the data analysis technique used is the F test to determine the effect of variables simultaneously. Based on the data from the results of the calculation obtained from the results of the F count test = 27.015> F table = 3.12, at a significant level obtained 0,000 <0.05 has a contribution of 40% so that it can be said that there is a significant influence of tutoring and supervision of parents simultaneously students' motivation to study in Public Elementary Schools in Tenggarong industrial area.